Prevention of yhe human papillomavírus lnfection - Eluf Neto, José; Zeferino, Luiz C.; Dores, Gerson B.; Passos, Mauro Romero Leal (Brazilian Journal of Sexually Transmitted Diseases, 2000)
lt is presented a up to date revision of literature about prevetion methods of HPV infcction. lt is also shown controversies and perspectives on management of HPV infection. [...]